The vanishing generation : faith and uprising in modern Uzbekistan - Bukharbayeva, Bagila (Indiana University Press, 2019)
As a young reporter in Uzbekistan, Bagila Bukharbayeva was a witness to her countrys search for an identity after the collapse of the Soviet Union. While self-proclaimed religious leaders argued about what was the true Islam, Bukharbayeva shows how some of the neighborhood boys became religious, then devout, and then a threat to the country's authoritarian government. The Vanishing Generation provides an unparalleled look into what life is like in a religious sect, the experience of people who live for months and even years in hiding, and the fabricated evidence, torture, and kidnappings that characterize an authoritarian government. In doing so, she provides a rare and unforgettable story of what life is like today inside the secretive and tightly controlled country of Uzbekistan. Balancing intimate memories of playmates and neighborhood crushes with harrowing stories of extremism and authoritarianism, Bukharbayeva gives a voice to victims whose stories would never otherwise be heard.